The prevalence of moderate-severe premenstrual syndrome and premenstrual dysphoric disorder and the related factors in high school students: A cross‐sectional study - Farzaneh Babapour; Forouzan Elyasi; Zohreh Shahhosseini; Monirolsadate Hosseini Tabaghdehi (Wiley, 2023)
Abstract Objective Premenstrual syndrome (PMS) is a clinical condition with physical and psychological symptoms affecting female students' quality of life, social activity, and school performance. Since most studies have focused on adult women, this study aimed to evaluate the prevalence of moderate-severe PMS, premenstrual dysphoric disorder (PMDD), and their related factors in high school students. Methods The participants of this cross‐sectional study, conducted in 2019, were 900 high school students in Sari, north of Iran. They were selected by census method from six high schools. Data were collected using Premenstrual Syndrome Screening Tool and General Health Questionnaire. Results The prevalence of moderate-severe PMS and PMDD were 33.9% and 12.3%, respectively. According to the logistic regression model, dysmenorrhea was significantly associated with a higher prevalence of moderate-severe PMS [adjusted odds ratio (AOR) 2.356, confidence interval (CI): 1.706-3.254, p < 0.0001] and PMDD (AOR: 1.924, CI: 1.186-3.120, p = 0.0008). Moreover, optimal general health was associated with a lower prevalence of moderate-severe PMS (AOR: 0.326, CI: 0.221-0.480, p < 0.0001) and PMDD (AOR: 0.309, CI: 0.161-0.593, p < 0.0001). The findings revealed that a family history of PMS and adding excess salt to the food were associated with a higher prevalence of PMDD (p < 0.05). Conclusion Although many high school students do not meet the criteria for PMDD, many experience PMS, which could be diminished with proper diet and improved general health.